Analisis Kepuasan Pengunjung Terhadap Objek Wisata Pantai Tapak Hantu Ditinjau Dari Aspek Rekreasi Wisata Pantai Kabupaten Bangka Tengah - khudori mustofa; Okto Supratman; Arthur M farhaby; Okto Supratman (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Tapak Hantu Beach has the potential to be developed into a leading tourist attraction in Bangka Tengah Regency. However, to accommodate this, it is necessary to conduct research. This study aims to analyze the quality of services and facilities on the Tapak Hantu beach, Bangka Tengah Regency. The research time was carried out in November 2022 which was carried out for two weeks the research method was carried out using theImportance and Performance Analysis Method (IPA). Based on the results obtained for the level of importance of service quality, namely with an average of x Ì… 3.71 and y Ì… 4.78 while for the value of the level of importance of the facility x Ì… 3.97 and y Ì… 4.55. So it can be concluded that the level of consumer satisfaction is actually lower than the level of expectations